1992
DOI: 10.1111/j.1365-2591.1992.tb01158.x
|View full text |Cite
|
Sign up to set email alerts
|

The apical seal of root canal sealing cements using a radionuclide detection technique

Abstract: The aim of this study was to evaluate the apical seal obtained with various root canal sealing cements using a new method based on the use of a radionuclide and an external detection technique. A total of 150 maxillary incisors and canines, which had been kept in saline solution, were used. The root canals were instrumented with a stepback technique and circumferential filing. Six experimental groups and two control groups were randomly formed. Each experimental group was obturated by a lateral condensation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Some studies report the apical seal of resin-based sealers to be superior to that of other sealers (17,18). In contrast, other studies have shown that the calcium hydroxide based sealer, Sealapex, provides a significantly better seal than others, including resin-based sealers (19,20). In our study, AH Plus showed also significantly more leakage when compared to Sealapex but there was no significant difference with Rocanal 2 and RC Sealer based sealers for each period.…”
Section: Discussioncontrasting
confidence: 63%
“…Some studies report the apical seal of resin-based sealers to be superior to that of other sealers (17,18). In contrast, other studies have shown that the calcium hydroxide based sealer, Sealapex, provides a significantly better seal than others, including resin-based sealers (19,20). In our study, AH Plus showed also significantly more leakage when compared to Sealapex but there was no significant difference with Rocanal 2 and RC Sealer based sealers for each period.…”
Section: Discussioncontrasting
confidence: 63%
“…1967, Nguyen 1987, Ingle & Bakland 1994). Gutta‐percha and endodontic sealers are currently the most common materials used to fill root canals (Nguyen 1987, Canalda‐Sahli et al. 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of gutta‐percha with sealer is the most common method of filling the root‐canal system (Canalda‐Sahli et al . 1992).…”
Section: Introductionmentioning
confidence: 99%